PROBLEMATIKA PERLINDUNGAN KONSUMEN TERHADAP PRODUK OVERCALIM DALAM PRESFEKTIF UNDANG-UNDANG PERLINDUNGAN KONSUMEN - SUPU, YUNIAR (Ganec Swara, 2025)
This research aims to analyze the problematic consumer protection of overclaimed products in the perspective of the Consumer Protection Law in Indonesia. Overclaims, which refer to excessive claims regarding the superiority of products, often deceive consumers and have the potential to harm them. The research method used is normative juridical with statutory and conceptual approaches. The results show that legal protection for consumers is divided into two categories: preventive legal protection and repressive legal protection. Preventive protection includes the provision of accurate information and a prohibition against misleading marketing practices. Meanwhile, repressive protection involves dispute resolution through litigation and the application of sanctions for businesses that overclaim. The liability of business actors related to overclaims is regulated in Article 19 of Law No. 8/1999, which obliges them to provide compensation to aggrieved consumers. This research also identifies the importance of increasing consumer awareness of their rights and the need for stricter supervision of business actors. Thus, this research is expected to provide recommendations for the improvement of consumer protection policies that are more effective in dealing with the issue of overclaims.